EVALUATION OF ADULT AND NON-FORMAL EDUCATION PROGRAMME IN OYO STATE, NIGERIA (2011)
The challenge of high rate of illiteracy in the developing nations necessitated the establishment of Adult and Non-Formal Education Programme. The programme is to organise literacy training, develop the trainees’ attitudes and commitments towards active participation in the development of their locality, improve the trainees’ job performance and standard of living as well as promote functional literacy in health education. Although Oyo State established the programme in 1988, there is no record that it has been empirically evaluated. Hence the study evaluated the programme to ascertain the achievement of the set objectives and the effect of trainees’ academic needs, trainers’ experience and qualification, training facility and training strategy on the trainees’ achievement in communication, numeracy, social studies and health education. The study adopted a survey research design. Multistage and proportionate stratified sampling were used to select 780 trainees, 30 trainers from 3 strata (Basic, Post Basic and Advanced literacy) and 40 primary six pupils spanning 10 local government areas of Oyo State. The four instruments used for data collection were: Adult and Non-Formal Education Trainees’ Questionnaire (r=0.80), Adult and Non-Formal Education Teachers’ Questionnaire (r = 0.83), Classroom Interaction Scale (r=0.62), Adult and Non-Formal Education Programme Achievement Test (r=0.75). Three research questions were answered and one hypothesis was tested. Data were analysed using descriptive statistics, t-test and multiple regression. The objectives of the programme were achieved to a great extent: literacy trainings (78.8%), trainees’ job performance (93.6%); trainees’ participation in the development of their environment (99.6%); trainees’ standard of living (97.1%) and functional literacy in health education (87.2%). Trainees academic needs, trainer’s experience and qualification, training facility and training strategy had composite effect on the achievement in communication [F(5,774)=3.03; p<0.05], numeracy [F(5,774)=12.27; p<0.05] social studies [F(5,774)=4.83; p <0.05] and health education [F(5,774)=8.96; p<0.05]. Training strategy (β=0.37, t=11.19, p<0.05), training facility (β=0.15; t=3.23; p<0.05), and trainers experience (β=0.11, t=3.06, p<0.05) contributed significantly to the trainees achievement in communication. In numeracy, trainer’s qualification (β=0.15, t=3.94, p<0.05) training strategy (β=0.12, t=3.47, p<0.05) trainees need (β=0.10; t=1.99, p<0.05) and trainers experience (β=0.08; t=-2.27, p<0.05) contributed significantly. Training facility (β=0.12, t=2.54, p<0.05) and trainers’ strategy (β=0.11, t=2.98, p <0.05) contributed significantly to the achievement in social studies. Health education showed that, facilities (β=0.19; t=4.15; p<0.05), training strategy (β=-0.13, t=-3.81, p<0.05), trainers’ qualification (β=-0.11, t=-2.90, p<0.05) and trainers experience (β=-0.08, t=-2.15; p<0.05) contributed significantly. There was no significant difference between the achievement of advanced literacy trainees and that of primary six pupils in communication, social studies and health education. However numeracy achievement of advanced literacy trainees was statistically different from that of primary six pupils (t=4.41; p<0.05). The programme, to a great extent has contributed towards the promotion of functional literacy in Oyo State. Government should therefore continue to encourage and support all aspects of the programme. Specifically, seminars and workshops should be organised for the trainers to improve their teaching skills.